(untitled) (LACCEI, 2024)
The objective of the research was to design a strategic planning model for the competitiveness of a small and medium-sized commercial sector enterprise. A cross-sectional, descriptive, non-experimental study was carried out by applying a questionnaire validated by expert judgment to 98 customers (Cronbach’s alpha 0.852). The internal analysis (MEFI) resulted in 2.24, and the external analysis (MEFE) in 2.58, with an MPC matrix of 3, which determines that the company adapts to its competitive environment. Strategies and strategic objectives were selected and aligned through the PEYEA matrix, showing a position with low turbulence and a competitive advantage. The MIE analysis indicated selective development for growth with a cost of S/5,659. The ecological and social impact was also evaluated, showing the importance of an eco-friendly mindset and a good working environment.